2020
DOI: 10.1029/2019jf005192
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling the Role of Inertia, Friction, and Cohesion in Dense Granular Avalanche Pressure Build‐up on Obstacles

Abstract: Understanding the physical processes involved in snow avalanche‐obstacle interaction is essential to be able to estimate the pressure exerted on structures. Although avalanche impact pressure has been measured in field experiments for decades, the underlying physical principles are still elusive. Previous studies suggest that pressure is increased due to the formation of an influenced flow region around the structure, the mobilized domain, which varies in size depending on snow properties such as snow cohesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…As aforementioned, the advantage of this approach is that parameters of the Sticky Hard Spheres model (volume fraction and coordination number) can be directly evaluated based on X-ray tomographic images by matching correlation functions 31 . While several recent numerical studies have analyzed the mechanical response of porous brittle solids like snow based on the real samples’ microstructures 18 , 19 , 21 , it has been recently shown that simplified structures made of spherical particles can be used to reproduce accurately important features of snow mechanics in the brittle range for different processes: failure initiation 35 , 36 , crack propagation 9 , 10 , snowflake fragmentation 37 , wind blowing snow 38 , snow granulation 39 and avalanche impact pressures 40 . One the one hand, this simplification makes us loose important information about the microstructure.…”
Section: Discussionmentioning
confidence: 99%
“…As aforementioned, the advantage of this approach is that parameters of the Sticky Hard Spheres model (volume fraction and coordination number) can be directly evaluated based on X-ray tomographic images by matching correlation functions 31 . While several recent numerical studies have analyzed the mechanical response of porous brittle solids like snow based on the real samples’ microstructures 18 , 19 , 21 , it has been recently shown that simplified structures made of spherical particles can be used to reproduce accurately important features of snow mechanics in the brittle range for different processes: failure initiation 35 , 36 , crack propagation 9 , 10 , snowflake fragmentation 37 , wind blowing snow 38 , snow granulation 39 and avalanche impact pressures 40 . One the one hand, this simplification makes us loose important information about the microstructure.…”
Section: Discussionmentioning
confidence: 99%
“…In [ 20 ] we implemented a similar setup consisting only of the second simulation phase described above. There we showed that the presented numerical procedure is able to reproduce impact pressure of snow avalanches measured in full-scale field experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The most important contact and particle properties are summarized in Table 1 . A more in-depth description of the parameter choices and the contact model can be found in [ 20 ] and its supplementary material.…”
Section: Methodsmentioning
confidence: 99%
“…Both discrete and continuous numerical methods have been developed to study avalanches. The discrete element method (DEM) assumes a discontinuous granular medium, which facilitates the recovery of microscale features and offers insights into local rheology of an avalanche (Kneib et al 2019;Kyburz et al 2020;Macaulay and Rognon 2020). However, the high computational cost of DEM limits its application to real-scale investigations.…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of the elastoplastic model that retrieves the mixed-mode failure of snow, the failure patterns after avalanche release are explored for the modeled snow avalanches. Furthermore, avalanche density variation, which plays a crucial role in altering flow regime, run-out distance, and impact pressure (Buser and Bartelt 2015;Kyburz et al 2020;Issler and Gauer 2008), are scrutinized throughout the flowing process. In addition, snow avalanche deposits are analyzed, to provide meaningful inferences on flow mechanisms and flow regimes (Issler et al 2020;.…”
Section: Introductionmentioning
confidence: 99%